Research Trends in Smart Workflow Automation: A Bibliometric Study from Scopus - Judijanto, Loso; Qadriah, Laila (Eastasouth Institute, 2025)
This study presents a comprehensive bibliometric analysis of smart workflow automation research using Scopus-indexed publications to map its intellectual structure, thematic evolution, and global collaboration patterns. A dataset covering the period 2000–2025 was extracted, cleaned, and analyzed using VOSviewer for science mapping and Microsoft Excel for performance metrics. Results reveal that the field is anchored by core concepts such as automation, internet of things, machine learning, and work-flows, which consistently occupy central positions in the research network. Emerging themes, including blockchain, supply chains, security, and ubiquitous computing, reflect a shift toward secure, interconnected, and efficiency-driven automation ecosystems. Co-authorship and country collaboration analyses highlight the pivotal roles of the United States, China, and Germany, supported by extensive cross-border partnerships. Temporal trend mapping demonstrates a transition from early industrial automation and foundational cyber-physical infrastructure toward integrated, value-oriented applications. The study offers practical guidance for industry adoption strategies, enriches theoretical understanding of the field’s conceptual landscape, and identifies promising research frontiers for future exploration.